Pengembangan Media Pocket Book Berbasis Discovery Learning terhadap Kemampuan Pemahaman Matematis - Dea Armelia; Iwit Prihatin; Utin Desy Susiaty (Universitas Indraprasta PGRI Jakarta, 2019)
The purpose of the research in the study was to study the development of learning discovery-based pocket book media on students' mathematical understanding abilities. The research methodology used is the method of research and development (R & D). Based on the results of development, research, and discussion, it can be concluded that the development of learning discovery-based pocket book media on mathematical understanding skills reaches a level of validity with excellent categories and achieves practicality with very practical criteria